Design and development of a liquid nitrogen cooled test cryopump for application in Steady-state Superconducting Tokamak-1. (June 2022) - Gangradey, Ranjana; Mukherjee, Samiran S.; Gupta, Vishal; Panchal, Paresh; Nayak, Pratik; Mishra, Jyoti S.; Dewasi, Avijit; Verma, Shashi Kant
Abstract: Cryocoolers and liquid helium cooled sorption cryopumps are widely used for the generation of high and ultra-high vacuum in large size experimental systems. Application areas of the sorption cryopumps using only liquid nitrogen is not explored much. Aiming to that, liquid nitrogen cooled test cryopump is designed, developed and fabricated to confirm the application feasibility on Steady-state Superconducting Tokamak-1 (SST-1) for pumping nitrogen and water vapor. After rough vacuum, base pressure ≤2.0E-7 mbar is achieved in the pumping dome using the cryopump. In addition, the pumping performance tests of the cryopump were carried out as per the AVS recommended method. The system offers pumping speed of ∼3616 l/s for nitrogen gas and 15928 l/s (N2 equivalent) for water vapor using liquid nitrogen only and the temperature on the panels were 80–81 K. Adsorption capacity for nitrogen gas was tested up to 6123 mbar-l and maximum gas load applied was 8.0E-2 mbar-l/s. In this paper, the pump design concept, analysis, pumping speed simulations, selected sorbent application and experimental investigations are discussed systematically. Highlights: LN2 cooled test cryopump is developed to confirm the applicability on SST-1 Tokamak for pumping nitrogen and water vapor. Fabrication details, operational concept and thermo-structural analysis results are discussed. The system offers pumping speed of ∼3616 l/s for nitrogen gas and ∼15928 l/s for water vapor using liquid nitrogen. Adsorption capacity for nitrogen gas was tested up to 6123 mbar-l and maximum gas load applied was 8.0E-2 mbar-l/s.